2021
DOI: 10.1007/s10096-021-04211-8
|View full text |Cite
|
Sign up to set email alerts
|

A decade of neonatal sepsis caused by gram-negative bacilli—a retrospective matched cohort study

Abstract: This study is to determine the incidence and outcome of neonatal gram-negative bacilli (GNB) sepsis in Stockholm, Sweden, and describe bacterial characteristics. This is a retrospective cohort study. All infants with GNB-sepsis between 2006 and 2016 were included and matched with two control groups, with suspected sepsis and uninfected neonates, respectively. Outcome was death before discharge, risk of death within 5 days after sepsis onset, and morbidity. The resistance pattern from all GNB was collected, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…This could be attributed to prematurity, low birth weight, and unhygienic conditions during delivery (especially in resource-poor settings). On the contrary, other studies have reported a higher occurrence of LOS than EOS [ 22 , 23 ]. The bacteriological profile of EOS differs from that of LOS as the mode of infection is different [ 24 ].…”
Section: Discussionmentioning
confidence: 75%
“…This could be attributed to prematurity, low birth weight, and unhygienic conditions during delivery (especially in resource-poor settings). On the contrary, other studies have reported a higher occurrence of LOS than EOS [ 22 , 23 ]. The bacteriological profile of EOS differs from that of LOS as the mode of infection is different [ 24 ].…”
Section: Discussionmentioning
confidence: 75%
“…6,13 The mortality rate of gram-negative neonatal sepsis is high, even in HIC settings. 5,24 In fact, all sepsis-related mortality in our cohort was the result of gram-negative sepsis. The predominance of gram-negative bacteria as causative microorganisms in neonatal sepsis in LMIC has been extensively described.…”
Section: Discussionmentioning
confidence: 82%
“…There are other studies with similar positive blood culture reports [ 38 - 40 ]. Some studies mentioned above, however, showed a higher incidence of the gram-negative organism [ 38 , 40 - 42 ]. Figure 5 summarizes the findings of gender differences in NS incidence, symptoms, blood culture, and bacteria in this study.…”
Section: Discussionmentioning
confidence: 99%